Produksi Mie Protein Tinggi dari Terigu yang Difortifikasi Tepung Komposit dan Protein Kacang Hijau - Sukamto Sukamto; Rafida Azizah; Suprihana Suprihana; Fatimah Karim (Seminar Nasional Lahan Suboptimal, 2019)
Sukamto S, Azizah R, Suprihana S, Karim F. 2019.  Production of high protein noodles using wheat flour fortified with composite flour and mungbean protein. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 487-495. Palembang: Unsri Press. Consumption of noodles in Indonesia in 2018 ranks second in the world after China with consumption of 12.54 billion packs. The amount of consumption of instant noodles has caused an increase in the import of wheat because the main raw material for making noodles is wheat flour. In 2018 wheat imports are predicted to reach 11.8 million tons. To reduce the need for wheat there needs to be an alternative local raw material to replace it. This study aims to utilize cassava and corn flour as composite flour to make instant noodles, where Mung bean protein isolates (IPKH) and Na-alginate are used for binding and gelling agents. The study used an experimental method with factorial randomized block design (RBD). The first factor is mung bean protein isolates and the second factor is Na-alginate. Statistical analysis using variance analysis (Anova) followed by Tukey Test with α ≤ 5% if there is a difference. The results showed that the interaction of the use of 30% protein isolates combined with 0.2% Na-alginate to make instant noodles increased the protein content of noodles to 31.24%, water absorbtion during cooking ranged from 104.66%-157.33%, breaking power before cooking around 55.20 g/cm2-81.33 g/cm2. Taste, aroma and texture based on organoleptic tests rather like to like. Keywords: instant noodles, Na-alginate, protein isolates